Maturação de sementes de sabiá (Mimosa caesalpiniifolia Benth.) - Alves, Edna Ursulino [UNESP] (2003)
The objective of this research was to study the maturation process of the Mimosa caesalpiniifolia Benth. seeds. The seeds and fruits were collected from plants located at the Bujari sugar mill, Areia County ,State of Paraíba, Brazil. Were made sixteen weekly fruits and seeds harvests of starting from 105 days after anthesis (d.a.a.) in the period of August 9 up to November 22, 2001. Were evaluated the fruits and, seeds color; fruits and, seeds dimensions , the moisture content; the fruits and, seeds fresh and dry weight mass, the germination, the dormant seeds percentage; and the vigor expressed by the first germination count, length and the seedling fresh and dry weight mass. According to the obtained results, it was observed that the physiological maturity of Mimosa. caesalpiniifolia occurred from 154 d.a.a. extending up to 168 d.a.a. The harvesting cannot be delayed beyond 189 d.a.a. due to a great loss of fruits and seeds caused by natural dispersion. To avoid the influence of seed dormancy, the harvest must be done at 154 until 168 d.a.a. with germination of 80% and maximum accumulation of dry weight mass.